An Outbreak of Crimean-Congo hemorrhagic fever (CCHF) in South Africa in 2022 - Utkarsh Betodkar; Zonunsangi Khiangte; Vanlalrengpuia (University of New South Wales, 2023)
Crimean-Congo Hemorrhagic Fever (CCHF) is a vector-borne disease caused by a tick-borne virus (Nairovirus) of the Bunyaviridae family. The onset of CCHF is sudden, with initial signs and symptoms including headache, high fever, back pain, joint pain, stomach pain, and vomiting. As the illness progresses, large areas of severe bruising, and bleeds can be seen, with case fatality as high as nine to 50%. This watching brief describes the Outbreak of CCHF in South Africa in 2022. There are 2 reported cases of CCHF in South Africa, in September 2022 with the case fatality rate (CFR) of 50%. Second case was laboratory confirmed on 10th September 2022. Although there are currently only two CCHF cases reported in South Africa, the unknown source is of concern and should be considered a warning signal for increased numbers in the future. For prevention, individuals must avoid contact with the blood and body fluids of livestock or humans who show symptoms of infection. Agricultural workers and others working with animals should use insect repellent containing DEET (N, N-diethyl-m- toluamide) on exposed skin and clothing for preventing tick bites. It is important for healthcare workers to use proper infection control precautions to prevent occupational exposure. There is no safe and effective vaccine currently available for human use. Treatment for CCHF is primarily supportive, and appropriate treatment of secondary infections.